2020
DOI: 10.3390/ijerph17249441
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Performance, Intrinsic Motivation and Adherence in Athletes

Abstract: Sports performance depends on a complex interaction of variables, such as psychological, physical, technical and tactical abilities. The purpose of the three studies described in this article was to validate an instrument to measure perceived performance in athletes (studies 1 and 2), and to analyze the predictive power of perceived performance, basic psychological needs and intrinsic motivation on the intention to be physically active (which was used as a predictor of adherence to sport) (study 3). In study 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 51 publications
0
17
0
11
Order By: Relevance
“…This instrument consists of five items of a single factor (e.g., “I believe my performance is good”). All items are given on a Likert scale ranging from 1 (Strongly disagree) to 5 (Strongly agree) with the following phrase preceding each item, “In general, when I practice my sport during competition...” The Cronbach’s alpha for this scale’s reliability was found to be .88 (Lourenço et al, 2018); and in separate research, the Spanish version of the questionnaire also obtained good psychometric properties (Almagro et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This instrument consists of five items of a single factor (e.g., “I believe my performance is good”). All items are given on a Likert scale ranging from 1 (Strongly disagree) to 5 (Strongly agree) with the following phrase preceding each item, “In general, when I practice my sport during competition...” The Cronbach’s alpha for this scale’s reliability was found to be .88 (Lourenço et al, 2018); and in separate research, the Spanish version of the questionnaire also obtained good psychometric properties (Almagro et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, our main objective in this research was to study the predictive power of autonomy support on the athletes’ basic psychological needs, their autonomous motivation, and their perceived performance. Based on this objective and on prior research results (Almagro et al, 2020; Gillet et al, 2010; Jowett et al, 2017; Pope & Wilson, 2012; 2015; Pulido et al, 2018), we formulated the following hypothesis: The coach’s autonomy support, the satisfaction of basic psychological needs, and autonomous motivation will significantly predict the athletes’ perceived performance. In addition, based on the differences found in some studies on the athlete’s motivation as a function of gender (Amado et al, 2014; Deaner et al, 2016; Fortier et al, 1995), we sought to analyze the separate influence of the athlete’s gender in the proposed structural equation model.…”
Section: Introductionmentioning
confidence: 99%
“…SDT claims that the more self-determined the motivation, the more favorable the results (Vallerand, 1997). In sports, selfdetermining motivation is linked to a series of results, such as dropout (Pelletier et al, 2001), effort (Pope and Wilson, 2012), engagement (Podlog et al, 2015), persistence (Rottensteiner et al, 2015), enjoyment (Russell et al, 2017), burnout (Fagundes et al, 2021), perceived performance (Almagro et al, 2020), and mental health (Sheehan et al, 2018). These studies supported that the direct or indirect relationships between motivation and mental health during physical exercise are of great importance, and this complex association continues to arouse the interest of researchers.…”
Section: Motivational Outcomesmentioning
confidence: 99%
“…Researchers in the areas of physical activity (PA) and exercise have examined IM as a factor affecting participation and performance. Recently, it has been reported that IM was predictive of performance for athletes and their desire to continue engaging in PA 13 . Others found that lack of motivation was a main limitation of engaging in exercise programs 14 .…”
Section: Introductionmentioning
confidence: 99%